The Patient and Observer Scar Assessment Scale to Evaluate the Cosmetic Outcomes of the Robotic Single-Site Hysterectomy in Endometrial Cancer. Issue 1 (1st January 2018) - Corrado, Giacomo; Calagna, Gloria; Cutillo, Giuseppe; Insinga, Salvatore; Mancini, Emanuela; Baiocco, Ermelinda; Zampa, Ashanti; Bufalo, Arabella; Perino, Antonio; Vizza, Enrico
Abstract : Objective: The objective of this study was to evaluate the cosmetic outcome of robotic single-site hysterectomy (RSSH) in early-stage endometrial cancer. Methods: We prospectively collected patient demographics, operative times, complications, pathologic results, and length of stay on all patients who underwent RSSH for early-stage endometrial cancer. The Patient and Observer Scar Assessment Scale (POSAS) was used for the evaluation of the cosmetic outcome. Results: Forty-five patients were included in our study from January 2012 to October 2015. The median age of patients was 63 years (range, 35–84 years), and the median body mass index was 26.5 kg/m 2 (range, 18–39 kg/m 2 ). No laparoscopic/laparotomic conversion was registered. The median docking time, console time, and total operative time were 7 minutes (range, 4–14 minutes), 46 minutes (range, 20–100 minutes), and 90 minutes (range, 45–150 minutes), respectively. The median blood loss was 50 mL (range, 10–150 mL). Nine patients underwent pelvic lymphadenectomy, and the median number of pelvic lymph nodes was 13 (range, 10–32). The median time to discharge was 3 days (range, 2–6 days). No intraoperative complications occurred, whereas we did observe 1 early postoperative complication. The oncological outcome was directly comparable to the literature. Patients reported low pain scores and high satisfaction in terms of postoperative scarring. The POSAS scores confirmed excellent cosmetic outcome of RSSH. Conclusion: Robotic single-site hysterectomy provided an efficient option for gynecologic oncologic surgery. The POSAS revealed high objective and patient-evaluated outcome, and patients were highly satisfied with the overall outcome of the appearance of their scars.